Reflections of the loss of rumeli on the turkish poetry [Rumeli'nin kaybinin tÜrk şiirindeki akisleri] - (:unkn) unknown (My University, 2011)
Losing the land of Rumeli has had significant reflections on the Turkish poetry. Poets such as Riza Tevfik, Mehmet âkif, Aka Gündüz, Arif Nihat, etc. wrote poems on how much the sudden loss of Rumeli, which had long been under the Turkish rule, influenced the feelings of the Turkish people quite negatively. They harshly criticized the negligence and the incompetence of the rulers which accelerated the loss of the land during the Balkan War. One can easily observe the dramatic style in such poems. Poets such as Yahya Kemâl, Arif Nihat, Orhan Saik, Halide Nusret have expressed that the Turkish people- and especially those poets with a Rumeli origin- will continue longing for this land, no matter how many years have passed over the loss.
Keywords: Drama; Longing; Loss; Poetry; Rumeli; The balkan war.